Antigen 5 Allergens of Hymenoptera Venoms and Their Role in Diagnosis and Therapy of Venom Allergy - Blank, Simon; Bazon, Murilo Luiz; Grosch, Johannes; Schmidt-Weber, Carsten B.; Brochetto-Braga, Marcia Regina [UNESP]; Bilo, Maria Beatrice; Jakob, Thilo (Current Medicine Group, 2020)
Purpose of ReviewStings of Hymenoptera of the superfamily Vespoidea such as yellow jackets, paper wasps or stinging ants are common triggers for severe and even fatal allergic reactions. Antigen 5 allergens are potent allergens in the majority of these venoms with major importance for diagnosis and therapy. Reviewed here are the characteristics of antigen 5 allergens, their role in component-resolved diagnostics as well as current limitations of the available diagnostics for proper therapeutic decisions.Recent FindingsAntigens 5 are proteins of unknown function in Hymenoptera venoms with high allergenic potency. They represent key elements in component-resolved diagnosis to discriminate between honeybee and vespid venom allergy. However, due to their pronounced cross-reactivity, there are remaining diagnostic and therapeutic challenges that have to be addressed.SummaryAntigens 5 are highly relevant venom allergens of the Vespoidea superfamily. Although their use in component-resolved diagnosis facilitates dissection of cross-reactivity and primary allergy in double sensitization to honeybee and vespid venom, new diagnostic concepts are needed to discriminate between allergies to different vespid species.
Keywords: Antigen 5; Component-resolved diagnostics; Allergen cross-reactivity; Hymenoptera venom allergy; Polistes dominula venom; Yellow jacket venom